International relations : a very short introduction - Reus-Smit, Christian, 1961- (Oxford : Oxford University Press, 2020)
International relations affects everyone's lives: their security, economic well-being, rights and freedoms, and the environment they share. This book explores international relations' central concerns with the changing way that political authority is organised globally, and provides the theoretical tools to understand the dynamics of the field.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on April 2, 2020).
Keywords: International relations